Supporting Factors For Participation In Volleyball Extracurricular Training At Vocational Schools In The Gumelar Sub-District For The 2022/2023 Academic Year - Nurmajid, Iqbal; Kusmiyati, Kusmiyati; Saefulah, Dian Imam; Yulianto, Ari Gana; Haris, Iyan Nurdiyan (PT Mediatama Zayna Indonesia, 2024)
This study aims to assess the effectiveness of the supporting factors for the implementation of volleyball extracurricular training at vocational high schools in Gumelar District. The research method used is descriptive with a survey approach. Data was collected through questionnaires from the population of students involved in the volleyball extracurricular activity, totaling 82 students, using total sampling technique. Data analysis was conducted quantitatively in a descriptive manner and presented in percentage form. The results indicate that the supporting factors for the implementation of volleyball extracurricular training are categorized as